Ways of Students Training Aimed at Analytical Skills Development while Solving Learning Tasks; Procedia - Social and Behavioral Sciences; Vol. 206 : Linguistic and Cultural Studies: Traditions and Innovations, LKTI - Politsinsky E. V. Evgeny Valerievich (2015, 2015)
Title screen